Pengukuran Beban Kerja Mental dengan SWAT: Studi Empiris Divisi K3L PT PLN Unit Induk Distribusi Jawa Barat - Nugraha, Salwaa Roudhoh; Puspani, Nissa Syifa (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
The demand for achieving zero accident targets, coupled with various urgent tasks and frequent overtime work, has the potential to increase workload and stress among employees in the K3L (Occupational Health, Safety, and Environment) division at PT PLN (Persero) West Java Distribution Main Unit. Although the company has measured workload using work analysis forms and psychosocial assessments, this approach is considered to not fully represent the actual conditions as it primarily focuses on time aspects and stress levels. This research aims to complement the company's existing workload measurement methods with the Subjective Workload Assessment Technique (SWAT), which considers three main dimensions that is time load, mental effort load, and psychological stress load. The measurement results indicate that the mental effort load dimension has the highest percentage at 34.85%, followed by psychological stress load at 33.20%, and time load at 31.95%. These findings suggest that mental effort load is the dominant factor influencing the mental workload of K3L employees. Based on these results, this research provides recommendations for improvements focused on evaluating and adjusting administrative workload and strengthening managerial support. It is hoped that implementing these proposals can reduce mental workload and foster a more balanced, healthy, and productive work environment. Keywords: Stress, Subjective Workload Assessment Technique, Workload, Work